Effects of chromosome number reduction on mitotic and meiotic stability in fission yeast - Yueyue Jiang; Yanze Jian; Lingyun Nie; Xin Gu; Ziyi Lu; Yongkang Chu; Xing Liu; Xuebiao Yao; Jin-Qiu Zhou; Shengnan Zheng; Chuanhai Fu (Genome Biology)
Abstract Background Genetic information is stored on multiple chromosomes in eukaryotic organisms and is passed on to offspring through cell division. How chromosome number influences cell division and chromosome segregation is not yet understood. Results In this study, we use artificial chromosome-fusion fission yeast cells, which contain one or two chromosomes, as models to investigate the effects of a reduced chromosome number on mitosis and meiosis. In mitosis, chromosome number reduction, particularly full fusion into one chromosome, prolongs mitotic duration in a manner dependent on the spindle assembly checkpoint and improves chromosome segregation accuracy in spindle assembly checkpoint-deficient cells. By contrast, in meiosis, chromosome number reduction impairs prophase oscillatory nuclear movement, prolongs meiosis I duration but shortens meiosis II duration, and severely compromises meiosis I chromosome segregation. Conclusions Our work uncovers different effects of reduced chromosome number on mitotic and meiotic stability and offers insights into how organisms may select the appropriate number of chromosomes in evolution.